Mobile Information Systems II IFIP Working Conference on Mobile Information Systems, MOBIS 2005, Leeds, UK, December 6-7, 2005 - Krogstie, John; Kautz, Karlheinz; Allen, David (IFIP Advances in Information and Communication Technology, 2005)
Mobility is perhaps the most important market and technological trend within information and communication technology. With the advent of new mobile infrastructures providing high bandwidth and constant connection to the network from virtually everywhere, the way people use information resources for work and leisure is being radically transformed. The rapid developments in information technology, particularly communication and collaboration technologies, are substantially changing the landscape of organizational computing. Workers in any business area are becoming increasingly mobile. Workers in more and more areas will be required to act flexibly within the constraints of the business processes of the company (or companies) they are currently working for. At the same time they will often want to use the same information technology to support their private tasks. Over the last years, a new breed of information systems has appeared to address this emerging situation, referred to as mobile information systems. Specific applications are also being characterized as, among others, m-Commerce, m-Learning, and m-Business. This book contains the proceedings of the second IFIP TC8 Working Conference on Mobile Information Systems which was held in December 2005 in Leeds, UK and sponsored by the International Federation of Information Processing (IFIP). Mobile Information Systems II aims to: · Clarify differences and similarities between the development of mobile and more traditional information systems. · Investigate the organizational impact of mobile information systems. · Investigate the 'e to m shift' , for example in m-Commerce relative to e-Commerce. · Investigate mobile commerce applications combined with the advantages of mobile communications technologies, the drivers of which have been identified as ubiquity, accessibility, security, convenience, localization, instant connectivity, and personalization. · Evaluate existing and newly developed approaches for the analysis, design, implementation, and evolution of mobile information systems. · Investigate technical issues and the constraints they impose on mobile information systems functionalities and design.